2021
DOI: 10.13189/ujaf.2021.090325
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Firm-Specific and Macroeconomic Factors on Financial Distress Risk: A Case Study from Turkey

Abstract: The purpose of this study is to examine the impact of both firm-specific and macroeconomic factors on the financial distress risk of the firms listed in the Borsa Istanbul Small and Medium Enterprises (SMEs) Industrial Index over the period from 2010 to 2019. Generalized Method of Moments (GMM) estimator is used to determine the potential impact of firm-specific and macroeconomic factors on financial distress risk. The dependent variable used in the study is financial distress risk measured by Springate S scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
3
19
2
2
Order By: Relevance
“…This is like several studies conducted in different countries, including Ikpesu (2019), Dwiantari and Meaning (2021), Rafatnia et al (2021). In contrast to the results of research by Saputri and Asrori (2019), Ceylan (2021) shows that there is a positive relationship between liquidity and financial distress. Based on theoretical considerations and previous research which showed different results, however, companies with low liquidity tended to increase the likelihood that the company would experience financial distress because the company did not have sufficient funds to pay short-term obligations.…”
Section: Liquiditycontrasting
confidence: 94%
See 1 more Smart Citation
“…This is like several studies conducted in different countries, including Ikpesu (2019), Dwiantari and Meaning (2021), Rafatnia et al (2021). In contrast to the results of research by Saputri and Asrori (2019), Ceylan (2021) shows that there is a positive relationship between liquidity and financial distress. Based on theoretical considerations and previous research which showed different results, however, companies with low liquidity tended to increase the likelihood that the company would experience financial distress because the company did not have sufficient funds to pay short-term obligations.…”
Section: Liquiditycontrasting
confidence: 94%
“…Several previous studies conducted in different countries showed a negative relationship between profitability ratios and financial distress, namely in the research of Dwiantari and Artini (2021) in Indonesia, Ikpesu (2019) in Nigeria, Kamaludin et al (2019) in Malaysia, Rafatnia et al (2021) in Iran, and Charalambakis and Garrett (2019) in Greece. However, different results are shown by the research of Saputri and Asrori (2019) in Indonesia, Ceylan (2021) in Turkey. However, in signaling theory that high profitability reflects that the company can operate profitably to avoid the risk of financial distress.…”
Section: Profitabilitymentioning
confidence: 90%
“…Apabila inflasi tinggi dan kemungkinan perusahaan bangkrut semakin kecil maka akan tersampaikan isyarat yang meyakinkan untuk investor dalam berinvestasi di perusahaan. Penelitian Pertiwi (2018), Ceylan (2021), dan Taufik & Sugianto (2021) menyatakan kenaikan inflasi dapat menurunkan kemungkinan kebangkrutan sebuah perbankan. H 2 : Inflasi berpengaruh positif dan signifikan terhadap financial distress.…”
Section: Pengembangan Hipotesisunclassified
“…Sehingga apabila nilai perusahaan mampu memoderasi serta memperkuat pengaruh inflasi terhadap financial distress maka akan tersampaikan isyarat yang meyakinkan untuk investor dalam berinvestasi di perusahaan. Sejalan dengan penelitian Pertiwi (2018), Ceylan (2021), dan Taufik & Sugianto (2021) yang menyatakan bahwa naiknya tingkat inflasi akan membuat kemungkinan terjadinya financial distress semakin mengecil, serta penelitian Nisak (2021) dan Yulitasari & Yulistina (2019) menyatakan kenaikan nilai perusahaan akan mempengaruhi mengecilnya kemungkinan terjadinya financial distress. Jika dilihat maka kedua variabel sama-sama mempunyai pengaruh yang positif serta siginifikan terhadap financial distress.…”
Section: Pengembangan Hipotesisunclassified
“…In general, the results of research that investigates the relationship between macroeconomic variables and the stock market in emerging market countries, such as those conducted by Marane, B., & Asaad, Z. (2021) in India; Moradi (2021) in Iran; Bui & Nguyen (2021) in Vietnam; Gu, Zhu, & Wang (2022) in China; Naseer, et.al (2021) in Pakistan; Ceylan (2021) in Turkey; Gautam & Gautam (2021) in Nepal.…”
Section: Introductionmentioning
confidence: 99%